Investigation of Expectations and Satisfaction After Sinus Surgery for Chronic Rhinosinusitis - Mattos, Jose L.; Hopper, Haleigh; Soler, Zachary; Mace, Jess C.; Schlosser, Rodney J.; Payne, Spencer C.; Smith, Timothy L.; Mattos, Meghan K. (The Laryngoscope, 2025)
Objective To perform the first mixed‐methods analysis of patient expectations and satisfaction after endoscopic sinus surgery (ESS). Methods Semi‐structured interviews of subjects undergoing ESS were performed to understand pre‐operative expectations and 6‐month post‐operative satisfaction. Descriptive statistics, logistic regression, and mediation analyses were performed. Quantitative questions were followed by qualitative probes for subjects to expand on quantitative answers. Study sample size was determined by thematic saturation based on qualitative responses. Data visualization was used to triangulate quantitative and qualitative data wherein themes emerged. Results A total of 52 participants were included in the mixed‐method analysis, and 110 were included in the mediation analysis. 56% of participants were male, with an average age of 55.7 (SD ± 2.18). Mean change in SNOT‐22 was 20.8 (SD ± 3.74), and 25% of participants did not achieve a minimal clinically important difference (MCID). Of the participants who did not achieve MCID, 79% would still choose to have sinus surgery again. Qualitative interviews revealed multiple preliminary categories describing the patient experience with ESS. Regression analysis showed that the most important predictor of satisfaction was whether pre‐operative expectations were met (OR = 3.8, p < 0.001). In mediation analysis, the effect of the clinical outcome on patient satisfaction was completely mediated by pre‐operative expectations (indirect effect p = 0.009, direct effect p = 0.17). Conclusion Patient expectations and satisfaction are important yet understudied measures in CRS and ESS. In ESS, satisfaction with outcome is driven by the fulfillment of pre‐operative expectations. Aligning such expectations is the most important intervention a sinus surgeon can perform to maximize success. Level of Evidence 4 Laryngoscope, 135:555–561, 2025